2022
DOI: 10.1001/jamaneurol.2022.2909
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Safety and Efficacy of Crenezumab vs Placebo in Adults With Early Alzheimer Disease

Abstract: ImportanceAlzheimer disease (AD), a neurodegenerative disease characterized by β-amyloid plaques and τ tangles in the brain, represents an unmet medical need with no fully approved therapeutics to modify disease progression.ObjectiveTo investigate the safety and efficacy of crenezumab, a humanized monoclonal immunoglobulin G4 antibody targeting β-amyloid oligomers, in participants with prodromal to mild (early) AD.Design, Setting, and ParticipantsTwo phase 3 multicenter randomized double-blind placebo-controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 33 publications
3
59
0
Order By: Relevance
“…Although they decreased the incidence of ADCC, CDC, vasogenic edema, and microhemorrhage, these antibodies still did not demonstrate adequate therapeutic efficacy. 13,14 These findings indicate that merely reducing the risk of inappropriate proinflammatory response do not increase therapeutic efficacy, and other mechanisms may underlie clinical failures. In our present study, we showed that an IgG4 subtype Aβ-targeting antibody, A16I4, activated the complement system and increased microglial synapse elimination (Supplementary Figs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although they decreased the incidence of ADCC, CDC, vasogenic edema, and microhemorrhage, these antibodies still did not demonstrate adequate therapeutic efficacy. 13,14 These findings indicate that merely reducing the risk of inappropriate proinflammatory response do not increase therapeutic efficacy, and other mechanisms may underlie clinical failures. In our present study, we showed that an IgG4 subtype Aβ-targeting antibody, A16I4, activated the complement system and increased microglial synapse elimination (Supplementary Figs.…”
Section: Discussionmentioning
confidence: 98%
“…10,11 To overcome the side effects of immunotherapies, antibodies targeting Aβ N-terminus (such as bapineuzumab), or IgG4 and IgG2 subtypes such as crenezumab and ponezumab were applied in clinical trials. [12][13][14] However, these antibodies still failed to rescue cognitive deficits in AD patients although some side effects significantly reduced. Recently, antibodies targeting Aβ aggregates such as aducanumab and lecanemab showed some beneficial effects in rescuing cognitive deficits, but they still exhibited low efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…It is a human IgG1 antibody, targeting Aβ fibrils ( Figure 2 ), and it comprises both N-terminal and central amino acids of Aβ [ 57 ] In a recent press release, Roche declared, that the phase III Graduate studies with their mAb failed the primary endpoints of slowing clinical decline in patients with early, prodromal to mild AD [ 58 ]. Additionally for Crenezumab (AC Immune SA, Lausanne, Switzerland; Genentech, South San Francisco, CA, USA; Hoffmann-La Roche), a humanized IgG4 targeting Aβ oligomers as well as fibrils [ 59 ], the clinical phase III placebo-controlled study was not successful in reducing the clinical decline in participants with early AD [ 60 ]. Solanezumab (Eli Lilly & Co., Indianapolis, IN, USA), a humanized form of the murine monoclonal antibody m266 generated against Aβ13-28 has similar binding qualities as Crezenumab [ 61 ] and finalized its phase III trial in 2014 for mild to moderate AD.…”
Section: Current Treatment Strategies Targeting Aβmentioning
confidence: 99%
“…Over the past 15 years, much of this research has focussed on developing monoclonal antibodies as potential disease modifying treatments (DMTs) targeting Aβ. 4 However, a number of trials of similar molecules did not meet the primary endpoint or were pulled midway after interim futility analyses, [5][6][7] leading to questions about whether this was the right approach given the complex and multifactorial pathogenesis of AD.…”
mentioning
confidence: 99%